Forums

Reed solomon generator polynomial

Started by Unknown January 28, 2005
hi all,

I have a generator polynomial in the format
G (X) =3D (X-=B5j )(X-=B5j+1)......(X-=B5j+2t-1), and, if j=3D1,
how can i get the equation in this format
g (X) =3D gn-kXn-k +gn-k-1Xn-k-1 + ........ g2X2+g1X + g0.

>>>>> "sudeepts" == sudeepts <sudeepts@gmail.com> writes:
sudeepts> hi all, sudeepts> I have a generator polynomial in the format sudeepts> G (X) = (X-&#2013266101;j )(X-&#2013266101;j+1)......(X-&#2013266101;j+2t-1), and, if j=1, sudeepts> how can i get the equation in this format sudeepts> g (X) = gn-kXn-k +gn-k-1Xn-k-1 + ........ g2X2+g1X + g0. You can do this by multiplying the product out. Or use the fact that g0 = product of all the uj's, gn-k-1 is sum of the uj's and so on. Ray